Prospects of Technology Adoption in Small Pump Schemes in the River Nile State, Sudan - Ahmed, Abdelmoneim Taha; Hashim, Abdelaziz A. (University of Khartoum Journal of Agricultural Sciences, 2023)
Linear programming was used to simulate the farming systems of small pump schemes in Shendi area, River Nile State, Sudan, to assess the prospects for technology use in cool-season food legumes and wheat. Different production activities, with respect to target crops, were identified to reflect different technology levels. The model constraints were the pump capacity, the scheme size and family labour. Alternative versions of the model were developed to examine possible production options that exist and to examine the effects of alternative resource levels and policy options, which are likely to affect adoption. The model results revealed that while farmers’ traditional practices were not economically feasible options, tendency is for adoption of medium rather than the recommended high technology levels. This reflects actual farmers’ behaviour, particularly for irrigation water, and indicates that water is the main resource constraint. The results also showed that the technology is not well supported by the traditional institutions of production relations, which create conflicting perception between resource owners towards technology use.